A survey and assessment of grasshoppers’ population in various sugarcane growing areas of Harion municipality in Sarlahi district, Nepal - Paudel, Kapil; Dangi, Naresh; Ansari, Anisur Rahman; Regmi, Rashmi (Journal of Agriculture and Natural Resources, 2020)
A small-scale study of grasshopper populations was undertaken in Harion municipality of Sarlahi district to ascertain whether grasshopper population in sugarcane growing areas is changing in consecutive years 2014 and 2015. The regular sugarcane growing areas were randomly selected and the survey was conducted to estimate the population in those consecutive years in 14 different locations where outbreak of Hieroglyphus banian (Fabricius) has occurred. The per square meter population was estimated using a ‘T’ shape which was made by tying 1m long two sticks to estimate one square meter area. The population of two consecutive years was compared to study the relationship between two years populations. The grasshopper infestation by risk category indicated that infestation warranted rating of severe in ward seven, eight and nine for 2015 from the population of 2014 AD. For 2016 AD, the risk was found low as most of the areas was categorized as moderate to light category as the population was found low in 2015 AD. Grasshopper population densities were found higher in some areas of Sarlahi district in the first year as compared to the second year. The population level in the first year was not found to induce population in next year as the population decreased in the second year. The trend of grasshopper population was not so threatening as the population was not found increasing in these years so was risk for next year. This might be due to the management of grasshoppers in nymphal stage in previous year, weather parameters, location, inter-cultural operations, decreasing of the rationing crops or presence of natural enemies. These findings provide guidance for the farmers in relation to grasshopper management and for future survey programs in relation to targeting regions of the district at risk from grasshoppers.